The single moving dipole source for electrocardiography inverse problem in 3D human model - Trung, Dang Thanh; Bao, Pham Thi Mai; Loc, Nguyen The (VNU Journal of Science: Mathematics - Physics; Vol 26 No 4, 2010)
Abstract